Proceedings of the 33rd Annual ACM Conference on Human Factors in Computing Systems 2015
DOI: 10.1145/2702123.2702288
|View full text |Cite
|
Sign up to set email alerts
|

Towards Multimodal Affective Feedback

Abstract: We explored how emotional cues presented in visual and haptic modalities interact. We constructed an affective haptic dataset, and used the emotional visual stimuli from the International Affective Picture System (IAPS). Participants were asked to rate the visual stimuli, haptic stimuli and visualhaptic stimuli. Analysis of the results indicated that the presence of haptic stimulus affects the arousal of the visual stimulus, but does not affect the valence significantly. We further explored this interaction in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…There is also a roughly even number and spread of stimuli in each of the four quadrants, although the bottom-left remains slightly sparser. These results are significant and promising, as the top-right and bottom-left quadrants have proven difficult to access in other research [3,49,51,53], and no other research has found such an even spread of stimuli throughout the model.…”
Section: Discussion: Comparing To Individual Modalitiesmentioning
confidence: 64%
See 4 more Smart Citations
“…There is also a roughly even number and spread of stimuli in each of the four quadrants, although the bottom-left remains slightly sparser. These results are significant and promising, as the top-right and bottom-left quadrants have proven difficult to access in other research [3,49,51,53], and no other research has found such an even spread of stimuli throughout the model.…”
Section: Discussion: Comparing To Individual Modalitiesmentioning
confidence: 64%
“…Our multimodal combinations, or multi-moji, have led to a wider range of conveyable emotional states than individual modalities are capable of, mostly in the top-right and bottomleft quadrants of the valence-arousal model [31], which have traditionally been the areas most poorly covered by feedback in HCI [3,49,51,53]. This means that UI designers now have a much richer set of possible emotional cues to use, to expand the affective range of feedback.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations